Avaliação da remoção de micropoluentes emergentes e nitrogênio em sistemas anaeróbios e microaeróbios seguidos de filtros biológicos percoladores sujeitos à aeração natural e forçada - Buarque, Patrícia Marques Carneiro (2017)
Inadequate discharge of effluents in natura or from sewage treatment stations (ETE) can lead to the introduction of various pollutants in the environment, such as organic and inorganic solids, carbonaceous organic matter, nutrients (eg nitrogen and phosphorus), among others . In recent years, especially in developed countries, concern has been growing with other types of pollutants, such as a category known as emerging micropollutants (ME), among which drugs (eg anti-inflammatory drugs and antibiotics) , various natural and synthetic hormones, as well as xenoestrogens (eg bisphenol-A). These MEs, even at low concentrations (ng / L or μg / L), may have adverse effects on aquatic organisms and humans such as genotoxicity and endocrine interference. Thus, the development and improvement of low-cost sewage treatment systems that are capable of removing conventional categories of pollutants, as well as MEs, are important. In this sense, the present work aimed to develop / improve a low cost system composed of UASB reactor operated under anaerobic and microaerobic conditions, followed by biological filtration percolator (FBP), with natural and forced aeration, for the joint removal of some ME and nitrogen. The experiments were run in a continuous stream, and the reactors were fed synthetic contaminated water containing a mixture of ME (estrone, estradiol, 17α-ethinylestradiol, trimethoprim, sulfamethoxazole, diclofenac and bisphenol-A), with approximately 200 μg / L of each (co-substrate) and macro and micro-nutrients, which contributed to the insertion of ammoniacal nitrogen (~ 60 mg / L) into the system. The UASB reactor, with a useful volume of 3.7 L, operated with TDH of 7 h and VOC of 3.7 kg / m3.dia. On the other hand, the FBP, with 38 L of useful volume and shavings of conduits as medium, worked with VOC of 0.03 kg COD / m3.dia and TAS of 0.32 m3 / m2.day, characterizing as a system of low rate. The research was carried out in seven phases, involving: acclimatization (Stage I); addition of micropollutants (Step II); addition of microaeration (Step III); insertion of the absorption column (Step IV); disengagement and reactivation of aeration in the column (Steps V and VI, respectively); and recirculation of the nitrificated effluent from the FBP to the UASB for denitrification (Step VII). The microbial population dynamics of the Bacteria and Archaea domains were evaluated using molecular techniques such as PCR / DGGE, in order to compare the treatments under anaerobic and microaerobic conditions. Finally, a life cycle assessment (LCA) was performed for the different treatment units and stages studied. The UASB-FBP system showed enough operational stability during all phases of operation, with removal of organic matter in the form of COD, higher than 90%, with most of the organic matter still being removed in the UASB reactor. It was shown to be inefficient in the removal of ME when operated under strict anaerobic conditions, with a maximum removal efficiency of 45% for estrone and a minimum of 3% for ethinyl estradiol. However, the microaeration greatly improved the degradation of these compounds in the anaerobic reactor, reaching mean removal efficiencies of more than 50% for all the compounds, which can be attributed to the change of metabolism of some common microorganisms of that medium, of O2. In all stages of operation, the removal of drugs and hormones in the FBP was very efficient, intensifying with the use of forced aeration, and consequent increase in the oxygen concentration dissolved in the liquid medium, with good removal efficiencies for the compounds evaluated (eg estrone-67% and bisphenol-A-91%). This increase in oxygen availability was also effective in the removal of nitrogen from the medium, allowing complete nitrification, approximately 60%. Recirculation of the nitrided effluent from the FBP to the UASB reactor for denitrification increased the removal of total nitrogen from the system, with global removals near 100% nitrate and 90% nitrite. Thus, the system under study has proved to be very attractive in all engineering and life cycle aspects evaluated and can be considered as a great low cost alternative of sewage treatment to be applied in the removal of conventional and unconventional pollutants.